2016
DOI: 10.3390/su8020119
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Energy-Optimized Urban Planning to Efficient Resource Use–A Case Study on Residential Settlement Development in Dhaka City, Bangladesh

Abstract: This study examines and explores the contribution of an energy-optimized urban planning approach to efficient resource use in the context of Dhaka city, Bangladesh. A conceptual energy optimization model called the "EnUp" model has been developed and tested for feasibility and adaptation strategies to improve urban energy use in residential settlements. This study is based on a system analysis and grounded theory approach that involved field methods including key informant (KI) interviews and collection of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The number of real estate companies has increased dramatically from only 42 in 1988 to more than 1500 in 2014. A recent study has identified 181 residential settlement development projects (plots and apartments) in the greater Dhaka city area [81].…”
Section: Formal Vs Informal Housingmentioning
confidence: 99%
“…The number of real estate companies has increased dramatically from only 42 in 1988 to more than 1500 in 2014. A recent study has identified 181 residential settlement development projects (plots and apartments) in the greater Dhaka city area [81].…”
Section: Formal Vs Informal Housingmentioning
confidence: 99%
“…For instance, in countries like Colombia, Chile, Mexico, Bangladesh, China, and Tanzania, the approach of grid expansion is an ongoing process, and large extensions of grid networks and power plants are under way [23,24]. One example of this is in Bangladesh, where energy optimization tools and planning have been researched in order to improve the electricity grid in Dhaka [25].…”
Section: Grid Base Electrificationmentioning
confidence: 99%
“…Second, the coordination between the different types of public facilities in recent years has been sought after [62,63], among them, the harmonious construction of medical facilities and pension facilities is worthy of attention. Third, it will be a valuable issue to discuss the planning and construction stages and the framework of stakeholder participation [64]. Furthermore, facility planning and construction is not only a spatial location issue, but also a social issue, herein it could involve the interests of existing residents, industrial and commercial enterprises, and other groups, particularly in the subsequent construction phase.…”
Section: Deficiency and Prospectmentioning
confidence: 99%